Protective effects of ethanolic extract of Piper cubeba L. on D-galactose induced neuronal lipofuscinogenesis in albino rats - Muchandi, Ashok A.; Dhawale, Shashikant C. (Science, Engineering and Health Studies, 2018)
Lipofuscin accumulation has been implicated in post-mitotic cell aging and neurodegenerative diseases like dementia and Alzheimer’s. The most characteristic feature of lipofuscin granules is auto-fluorescence. Many allopathic agents are available for treatment of dementia but having limited use. In the present study, the ethanolic extract of fruits of Piper cubeba L. belonging to family Piperaceae was evaluated for biochemical and histochemical changes of lipofuscin granules in the hippocampus region of albino rats against D-galactose induced neuronal lipofuscinogenesis. The results of the present study revealed that, dose 400 mg/kg, p.o. of plant extract significantly (P < 0.001) decreases lipofuscin fluorescence from the hippocampus region of albino rats when compared with D-galactose treated group. The histochemical observations showed increased accumulation of lipofuscin granules in D-galactose treated group animals whereas Piper cubeba co-treated group showed a decreased number of lipofuscin granules in hippocampus region of brain. A reference drug Piracetam 400 mg/kg, i.p. treated group animals also exhibited decreased accumulation of lipofuscin granules. Thus, protective effect of ethanolic extract of Piper cubeba on D-galactose induced neuronal lipofuscinogenesis may be due to presence of lignans like cubebin, hinokinin, yatein, isoyatein and their antioxidant property.